Utilization of Edible-Insects as Protein Substitute in Food and Effects of Processing on Their Nutrient Contents and Protein Functionalities - Nura Abdullahi; Enerst Chukwusoro Igwe; Munir Abba Dandago; Abdurrashid Rilwan; Hassana Jibril; Raliya Iliyasu (Food ScienTech Journal, 2022)
Population growth, poverty and climate change dictate the need for additional protein sources. Edible insects are potential protein substitutes and can provide both humans and animals with the required amount of protein, essential amino acids, and other indispensable nutrients. Incorporating edible-insects into familiar products and subjecting them to adequate processing that masks their natural appearance will improve their consumption. This article provides insights on the potentials of edible-insects as novel ingredients in food processing and its various benefits. Effects of processing on their nutritional and functional properties were also discussed. Literature was gathered through an online search on the Science Direct database and Google Scholar. Edible-insect powders, protein isolates and concentrates and oils were reported to be incorporated into bugger, chips, chocolate, bread, cookies, and other baked snacks. The addition of insect products improves protein, fat, fiber, and minerals contents. Insects also contain healthier lipids when compared with conventional proteins. Edible-insects will provide essential nutrients to the rapidly growing world population when more attention is given to their production, processing, safety, and marketing. Efforts need to be strengthened to secure global acceptance of insect protein since the conventional sources are not reliable and cannot satisfy the world population in decades to come.